Modelling resilient railway systems - Fecarotti, Claudia (2018)
The complexity of the railway asset management process motivates the need for bespoke tools to enable optimal asset management decisions. To address such a need, a Railway Asset Management Modelling Framework is presented to support a structured and systematic decision making process on asset interventions. The framework describes the structure and requirements of the railway asset management system for delivering a safe and reliable railway, whilst minimising the life-cycle costs. It specifies the models and data needed to predict assets’ and network performance indicators on a whole-life, whole-system basis. Depending on the level of abstraction, the models support decisions at asset/route/network level to ultimately meet service and safety targets for the minimum cost. Two main types of models are described: (i) predictive models to forecast the performance of the system of interest under a variety of circumstances, and (ii) optimisation models that use real and predicted data to achieve optimal decisions on the asset interventions. To the first group belong the asset state models aimed at assessing the assets’ response to a range of maintenance strategies.